Working from Home and Work–Family Conflict - Lass, Inga; Wooden, Mark (My University, 2022)
Longitudinal evidence on whether, and under what conditions, working from home is good or bad for family life is largely absent. Using 15 waves of data from the Household, Income and Labour Dynamics in Australia Survey, this study investigates the association between working from home and work–family conflict among parents. Fixed-effects structural equation models reveal that more hours worked at home are associated with less work–family conflict. This association, however, is only sizeable (and significant) for those working most of their hours at home. Furthermore, mothers benefit significantly more from home working than fathers. Additionally, mediation analysis suggests the association between working from home and work–family conflict is partly mediated by the level of schedule control, commuting time, and unsocial work hours. Whereas increased schedule control and less commuting among home workers reduce work–family conflict, home working is also associated with more unsocial work hours, which increases work–family conflict.
Work, Employment and Society
Keywords: Families and relationships; Labour market; Lifestyle